Análisis comparativo del papel del Estado, en la implantación del modelo económico circular. México-Colombia: 2018-2024 - Salazar Duarte, Cynthia Denisse (Universidad Autónoma Metropolitana, 2025)
This thesis conducts a comparative analysis of the role of the State in implementing the circular economy model in Mexico and Colombia between 2018 and 2024, highlighting the transformative potential of this approach to address social, economic, and environmental challenges. Through a detailed review, the advancements in each country are examined: Mexico, with its emerging legislative framework that includes the General Law on Circular Economy, and Colombia, a regional leader with a more consolidated National Strategy. Both contexts reveal complementary strategies that, despite their differences, aim for more sustainable and equitable development. The research emphasizes three key dimensions: social impact, regional impact, and the specific circumstances in each country, demonstrating how the circular economy can reduce inequalities, mitigate climate change, and foster community development. This study suggests that Colombia's experience can provide valuable insights to strengthen Mexico's institutional framework, while simultaneously highlighting Mexico's unique opportunities to lead transformations aligned with its environmental richness and biodiversity. Additionally, it stresses the importance of coordinated efforts among governments, civil society, and the private sector to turn the circular economy into a strategic development axis for Latin America. This work invites reflection on shared opportunities and challenges, towards a more prosperous and responsible future.; Esta tesis realiza un análisis comparativo del papel del Estado en la implementación del modelo de economía circular en México y Colombia entre 2018 y 2024, destacando el potencial transformador de este enfoque para abordar desafíos sociales, económicos y ambientales. A través de una revisión detallada, se examinan los avances en cada país: México, con su marco legislativo que incluye la Ley General de Economía Circular, y Colombia, líder regional con una Estrategia Nacional más consolidada. Ambos contextos revelan estrategias complementarias que, pese a sus diferencias, buscan un desarrollo más sostenible y equitativo. La investigación destaca tres dimensiones clave: el impacto social, regional y específico en cada país, evidenciando cómo la economía circular puede reducir desigualdades, mitigar el cambio climático y fomentar el desarrollo comunitario. Este estudio propone que la experiencia de Colombia puede ofrecer aprendizajes valiosos para fortalecer el marco institucional mexicano, y a su vez, resalta las oportunidades únicas de México para liderar transformaciones alineadas con su riqueza ambiental y biodiversidad. Así como la importancia de un compromiso coordinado entre gobiernos, sociedad civil y sector privado, para convertir la economía circular en un eje estratégico de desarrollo en América Latina. Este trabajo invita a repensar las oportunidades y desafíos comunes, hacia un futuro compartido más próspero y responsable.